About Academic Self-Efficacy with Peer Social Support for Students at SMP Negeri 14 Semarang - Diyah, Fatimahtus Sadiyah; Kusdaryani, wiwik; Maulia, Desi (Prodi Bimbingan dan Konseling universitas PGRI Semarang, 2024)
Problems that are often experienced by students at school are regarding assignments, student abilities and the beliefs that students have, which will certainly influence their learning potential, in this case the social support of peers is certainly very important in the learning process. The aim of this research is to determine the relationship between academic self-efficacy and peer social support.